Some thoughts on the Goldbach's Conjecture (Part III) - D’AMICO, Rosario (Journal of Mathematical Economics and Finance; Vol 5 No 1 (2019): JMEF, Volume V, Issue 1(8), Summer 2019, 2019)
This work aims to formulate considerations to demonstrate the Goldbach's Conjecture by using a demonstration process by making it easier than the usual temps already present in literature.